Peran Kebijakan Dividen sebagai pemoderasi terhadap Penentu Cash Holding - Stevanus, David; Susanto, Yulius Kurnia (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of this research is to obtain the empirical evidence about the effect profitability, leverage, capital expenditure, net working capital, investment opportunity set, firm size dan operating cash flows towards cash holding moderated by dividend policy to the effect of profitability, leverage and capital expenditure on cash holding. The population in this research is manufacturing companies listed in IDX from the year of 2019-2021. Samples were obtained through purposive sampling method in which 41 data were taken as the sample. This research uses multiple regression method to test the hypotheses. The results of this research indicated that leverage, firm size, operating cash flows affect cash holding and moderating dividend policy towards leverage affect cash holding, if leverage increases then cash holding decreases, if firm size and operating cash flows increases then cash holding increases, if dividend policy increases it will strenghten then relationship between leverage and cash holding while profitability, capital expenditure, net working capital, investment opportunity set, moderating dividen policy towards profitability and capital expenditure do not affect cash holding.